The Prevalence of Star-forming Clumps as a Function of Environmental Overdensity in Local Galaxies - Dominic Adams; Hugh Dickinson; Lucy Fortson; Kameswara Mantha; Vihang Mehta; Jürgen Popp; Claudia Scarlata; Chris Lintott; Brooke Simmons; Mike Walmsley (The Astrophysical Journal)
At the peak of cosmic star formation (1 ≲ z ≲ 2), the majority of star-forming galaxies hosted compact, star-forming clumps, which were responsible for a large fraction of cosmic star formation. By comparison, ≲5% of local star-forming galaxies host comparable clumps. In this work, we investigate the link between the environmental conditions surrounding local ( z < 0.04) galaxies and the prevalence of clumps in these galaxies. To obtain our clump sample, we use a Faster R-CNN object detection network trained on the catalog of clump labels provided by the Galaxy Zoo: Clump Scout project, then apply this network to detect clumps in approximately 240,000 Sloan Digital Sky Survey galaxies (originally selected for Galaxy Zoo 2). The resulting sample of 41,445 u -band bright clumps in 34,246 galaxies is the largest sample of clumps yet assembled. We then select a volume-limited sample of 9964 galaxies and estimate the density of their local environment using the distance to their projected fifth nearest neighbor. We find a robust correlation between environment and the clumpy fraction ( f _clumpy ) for star-forming galaxies (specific star formation rate, sSFR > 10 ^−2 Gyr ^−1 ) but find little to no relationship when controlling for galaxies’ sSFR or color. Further, f _clumpy increases significantly with sSFR in local galaxies, particularly above sSFR > 10 ^−1 Gyr ^−1 . We posit that a galaxy’s gas fraction primarily controls the formation and lifetime of its clumps, and that environmental interactions play a smaller role.